1935
DOI: 10.1084/jem.62.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Poliomyelitis Virus in Vitro by Crystalline Vitamin C (Ascorbic Acid)

Abstract: The experimental evidence presented in this paper shows that multiple paralytic doses of poliomyelitis virus, when mixed with very small amounts of crystalline vitamin C (ascorbic acid), are rendered non-infectious as determined by intracerebral injection of such mixtures into rhesus monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1936
1936
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Ascorbate is one of the early unorthodox therapies for infectious disease and cancer since its introduction in the first half of the 20th century [2][3][4][7][8][9]60,61]. This approach was subsequently promoted by Cameron and Pauling [5,6,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate is one of the early unorthodox therapies for infectious disease and cancer since its introduction in the first half of the 20th century [2][3][4][7][8][9]60,61]. This approach was subsequently promoted by Cameron and Pauling [5,6,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral properties of Vit-C help to reduce symptoms and mortality in children and adults [1][2][3][4]. The antiviral activities of ascorbic acid was known and it was published almost 80 years ago [5][6][7][8][9] when scientists were involved in work on poliomyelitis. Moreover, the use of ascorbic acid as a medicinally crucial agent against various diseases was also well established [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The controversy surrounding the claim of the antitumor effect of vitamin C has attracted a lot of public attentions (1)(2)(3). Despite reports on the antiviral (4)(5)(6) and antitumor (7)(8)(9) activities of ascorbic acid there is as yet no persuasive explanations of these biological effects at the cellular and molecular levels. Previous studies (9, 10) indicated a preferential cytotoxicity of ascorbate and copper ion against malignant melanoma cells with little effect on the proliferation of normal cells.…”
mentioning
confidence: 99%